Incorporation of 45S5 bioglass via sol-gel in β-TCP scaffolds: Bioactivity and antimicrobial activity evaluation - Spirandeli, B. R. (2021)
In this work, β-TCP (β-tricalcium phosphate) bioresorbable scaffolds were prepared by the gel casting method. Then, they were impregnated with a 45S5 bioglass sol gel solution to improve biocompatibility and promote bioactivity and antimicrobial activity. The β-TCP scaffolds had an apparent porosity of 72%, and after the incorporation of the bioglass, this porosity was maintained. The elements of the bioglass were incorporated into β-TCP matrix and there was a partial transformation from the β-TCP phase to the α-TCP (α-tricalcium phosphate) phase, besides the formation of bioactive calcium and sodium‑calcium silicates. The scaffolds β-TCP with 45S5 bioglass incorporated (β-TCP/45S5) did not show a reduction in their values of mechanical strength and Weibull modulus, despite the partial transformation to the α-TCP phase. Bioactivity, cell viability, and antimicrobial activity improved significantly for the β-TCP/45S5 scaffold comparing to the scaffold without the bioglass. The mineralization of carbonated hydroxyapatite was verified in Simulated Body Fluid (SBF). The cell viability, evaluated by the reduction of 3-[4,5-dimethylthiazol-2-yl]-2,5-diphenyltetrazolium bromide – MTT in MG63 cells, increased by 178%, and β-TCP/45S5 scaffold also enhanced cell activity and osteoblast differentiation observed by means of total protein contend and alkaline phosphatase activity, respectively. The formation of growth inhibition zones was also observed in the disk diffusion assay for three tested microorganisms: Staphylococcus aureus, Escherichia coli and Candida albicans. To conclude, the vacuum impregnation method in 45S5 bioglass sol gel solution was effective in penetrating all the interconnected macroporosity of the scaffolds and covering the surface of the struts, which improved their biological properties in vitro, bioactivity and antibacterial activity, without reducing mechanical strength and porosity values. Thus, the β-TCP/45S5 scaffolds are shown as potential candidates for use in tissue engineering, mainly in bone tissue regeneration and recovery.